Prevalência de intoxicações agudas auto referidas e fatores associados à contaminação por agrotóxicos em Mato Grosso - Silva, Daniely Oliveira da (2018)
The state of Mato Grosso is the largest consumer of agrochemicals in Brazil. With that, have an increased risk of exposure of populations to pesticide poisonings. The objective is to estimate prevalence and factors associated with acute poisoning by pesticides in Mato Grosso. This is an epidemiological survey carried out in six municipalities of Mato Grosso. The data were obtained from surveys done by the State Department of Health. Were realized Poisson Regression analyzes for the variables p-value <0.20. About 17% of respondents received a diagnosis were diagnosed with acute pesticide poisoning. The main associated factors were: reside near crops (RP= 2,81; IC95%: 1,79 - 4,41); own until incomplete high school (RP= 1,80; IC95%: 1,22 - 2,71); working less than 500 meters from maize crops (RP: 1,57; IC95%: 1,05 - 2,35); and cotton (RP: 1,43; IC95%: 1,02 - 2,02). In times of flexibility from the regulatory frameworks for agrotoxic use and freezing of investments in the area of health in Brazil, becomes increasingly complex the challenge of the SUS in dealing with questions related to the use of pesticides and their impacts on public health.